Local engagement in environmental peacebuilding: protected area development as a pathway to peace in Afghanistan. Issue 6 (18th August 2022) - Johnson, McKenzie F.
ABSTRACT: This article interrogates local engagement in protected area development as a mechanism for peacebuilding in Afghanistan. Using interviews with representatives from the Band-e-Amir Protected Area Committee, I argue that protected area engagement produced mixed outcomes. In one sense, local engagement generated confidence that democratic processes introduced through governance reforms could transform power structures and resolve conflict. Yet, these same processes eroded confidence in the state's ability to deliver benefits and serve as a foundation for peace. This case suggests a need to consider how environmental peacebuilding at subnational scales can impede post-conflict peacebuilding through its effect on state-society relations.